A hardware-in-the-loop rig for hardwareagnostic simulation of digital twins: The development of a hardware-in-the-loop rig for an autonomous electric race car of Chalmers formula student driverless - Ali Doosti, Alan; Ingemarsson, Gabriel; Lingestål, Elmer; Losman, Martin; Wennergren, Viktor; Örjas, André (My University, 2021)
Modern cars require a lot of resources to develop, and future fully autonomous cars will likely add further complexity. In order to limit the resources spent on development and testing with a real car on a real track, a technique called hardware-in- the-loop (HIL) can be used. This means testing new hardware and software on a separate build consisting of the same hardware as in a real car together with digital representations of hardware components not physically present, a digital twin. Chalmers formula student driverless (CFSD) is a project where master students from Chalmers University of Technology build their own autonomous race car and they could benefit from the concept of HIL for the same reasons that the industry does. By accessing the database of CFSD and getting involved in their project, while taking ethics into account, it should be possible for a group of bachelor students to provide them with a rig utilising the concept of HIL. This goal was not fully reached in the time scope of the bachelor thesis described in the report. Nevertheless, a foundation to build upon has been created, as well as hardware working as intended and successfully using the same software as the car.
Keywords: HIL; hardware-in-the-loop; CFSD; Chalmers formula student driverless; digital twin; autonomous race car; bachelor thesis